Evaluating modified grease traps with coconut coir for improved adsorption efficiency / Rosyidah Syahirah Binti Roslan, Mohd Izwan Masngut and Razi Ikhwan Md Rashid - Roslan, Rosyidah Syahirah; Masngut, Mohd Izwan; Md Rashid, Razi Ikhwan (Faculty of Health Sciences, Universiti Teknologi MARA, 2024)
Fats, oils, and greases (FOG) from restaurant wastewater can cause significant environmental and infrastructure issues. Grease traps are employed to prevent these pollutants from entering sewer systems. This study investigates the efficiency of conventional and modified grease traps enhanced with coconut coir activated carbon (CCAC) in treating restaurant wastewater. The objectives were to evaluate the effectiveness of both systems in reducing oil, grease, and turbidity levels. In the experimental setup, wastewater from a restaurant was treated using a standard grease trap and a modified trap with CCAC. Results showed that the conventional grease trap achieved an oil and grease removal efficiency of 89.54%, while the modified trap had a lower efficiency of 50.38%. However, the modified trap significantly improved turbidity reduction by 81.86%, compared to 24.64% in the conventional trap. Both systems showed no thermal influence on treatment. Overall, while the conventional grease trap was more effective at oil and grease removal, the addition of CCAC in the modified trap improved water clarity, suggesting a potential for combining both approaches to optimize wastewater treatment. This study emphasizes the importance of improving grease trap technologies to achieve better environmental sustainability in restaurant wastewater management.